UPAYA GURU BIMBINGAN DAN KONSELING DALAM MENGATASI SISWA YANG BERPERILAKU MENYIMPANG DI MTS AL MUDDAKIR BANJARMASIN - Sutinah Sutinah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2017)
Writing this thesis research entitled "Efforts Teachers Guidance and Counseling in Overcoming Students Behaving Behind in MTs Al-Muddakir Banjarmasin. This researcher to overcome the service of personal guidance and counseling to students who behave deviant and Know what are the constraints on the service of guidance and personal counseling to students who behave deviant in Mts Al Muddakir Banjarmasin.His guidance and counseling teacher proposes trying to cope with students who are deviant in school by providing services to learners and guidance and counseling teachers trying to develop proficiency and always learning from books, references and from the experience of science that has been obtained. Thus, personal counseling services according to guidance and counseling teachers have been effective to overcome students who behave deviant in MTs Al Muddakir Banjarmasin. Prevention efforts are easier to do than pursue efforts. Prevention efforts aim to prevent students from confusing their behavior with aberrant behavior. In addition, to make it easier for students to find the right model in the determination of behavior.